Preparation and Catalytic Performance of Cu-Doped TiO2-g-C3N4 Composites - Yang, Saihe; Zhang, Yifei (Journal of Theory and Practice of Engineering Science, 2023)
Photocatalytic methods present a viable solution for mitigating global energy deficits and environmental concerns. Therefore, it is crucial to develop effective photocatalytic systems and related materials. Among various options, semiconductor photocatalysts have gained attention due to their straightforward synthesis, economic viability, and eco-friendly nature. Key examples include the metal oxide semiconductor TiO2 and the non-metallic counterpart, g-C3N4. This research focuses on creating a TiO2/g-C3N4 binary heterojunction through a calcination process, subsequently incorporating copper (Cu) via photo-deposition to yield Cu/TiO2/g-C3N4 ternary composite nanomaterials. Material characterization techniques such as scanning electron microscopy (SEM), X-ray diffraction (XRD), and UV-Visible spectroscopy confirmed the successful formation of these composites, exhibiting increased specific surface areas and heightened responsiveness to visible light. Additionally, the efficiency of these Cu-doped composites was evaluated through rhodamine B degradation tests, demonstrating improved visible light absorption and overall superior photocatalytic performance.